A thematic review on interpretation perspective of UNESCO Global Geoparks over the past 5 years (2019-2024): analysis of trends for future studies - Zhang, Zoë Jiabo; Ismail, Mohd Hafizal; Jumaat, Noor Jalilah; Pan, Xiaoyang (Malque Publishing, 2025)
The interpretation of the geological, geomorphological, and archeological significance of these geosites will assist visitors in comprehending and appreciating their importance to our heritage and the significance of their protection for future generations. The apparent lack of attention to interpretation in the geopark field has raised concerns among researchers and park authorities about how to promote the most effective interpretation principles when interpretive design and practice are popularized, despite the promising development of interpretive research. This study evaluates articles published between 2019 and 2024 to explore how interpretation is addressed in the context of the UNESCO Global Geoparks. Using a thematic review methodology, this research incorporates keywords from the SCOPUS and WoS databases. The thematic review analysis revealed four key themes: effective interpretation, geoconservation and SDGs, geoeducation and awareness, and the promotion of geotourism. The findings provide valuable insights for park policymakers, visitors, practitioners, and researchers interested in the interpretation field related to UNESCO Global Geoparks.